Reflections of a cold warrior : from Yalta to the Bay of Pigs - Bissell, Richard M. (Richard Mervin), 1909-1994 (Yale University Press, 1996)
Richard M. Bissell, Jr., the most important CIA spymaster in history, single-handedly led America's intelligence service from the age of Mata Hari into the space age. Under his guidance the U-2 spy plane, the SR-71 "Blackbird," and the Corona spy satellite were developed, and the agency rose to the pinnacle of its power. Bissell was also, however, the architect of the infamous Bay of Pigs operation that failed to overthrow Castro in 1961 and led to the decline of the CIA. In this compelling memoir, Bissell gives us an insider's view of the personalities, policies, and historical forces surrounding these and other covert operations, and the lessons learned during those times of conflict